1997
DOI: 10.1029/97ja01675
|View full text |Cite
|
Sign up to set email alerts
|

MHD simulation of an interaction of a shock wave with a magnetic cloud

Abstract: Abstract. Interplanetary shock waves, propagating in the heliosphere faster than earlier-emitted coronal ejecta, penetrate them and modify their parameters during this interaction. Using two and one half dimensional MHD simulations, we show how a magnetic cloud (flux rope) propagating with a speed 3 times higher than the ambient solar wind is affected by an even faster traveling shock wave overtaking the cloud. The magnetic field increases inside the cloud during the interaction as it is compressed in the radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 10 publications
7
44
0
Order By: Relevance
“…However, the results of ejecta 1 in columns 2 and 4 were very different: due to the interaction with the shock wave driven by ejecta 2, ejecta 1 arrived at 1 AU compressed (with an approximate 79% smaller radial width) and with a much faster front speed (about 27% higher) and shorter transit time (about 10.5% less). These results agree with those by Vandas et al (1997), where they studied the interaction of a shock wave overtaking a magnetic cloud (MC) using a MHD model. They found that the passing of the shock through the MC produces an increment in the MC's field magnitude and the ejecta is compressed and accelerated in the radial direction.…”
Section: One-dimensional Simulationsupporting
confidence: 82%
“…However, the results of ejecta 1 in columns 2 and 4 were very different: due to the interaction with the shock wave driven by ejecta 2, ejecta 1 arrived at 1 AU compressed (with an approximate 79% smaller radial width) and with a much faster front speed (about 27% higher) and shorter transit time (about 10.5% less). These results agree with those by Vandas et al (1997), where they studied the interaction of a shock wave overtaking a magnetic cloud (MC) using a MHD model. They found that the passing of the shock through the MC produces an increment in the MC's field magnitude and the ejecta is compressed and accelerated in the radial direction.…”
Section: One-dimensional Simulationsupporting
confidence: 82%
“…These shocks are likely associated to each of the two CMEs. We note that, while the flux ropes of the two CMEs are not able to penetrate through each other, the CME-driven shock of CME2 might pass through the slower CME1 (Vandas et al 1997). …”
Section: Remote-sensing Observationsmentioning
confidence: 99%
“…8.ÈLASCO C2 images at 10 : 39 UT (left) and 10 : 54 UT (right), showing the halo CME on 2000 July 14. Burlaga 1982 ;Vandas et al 1997). The CME arrival was also accompanied by a severe magnetic storm, during which the Dst index decreased to [300 (see Fig.…”
Section: Halo Cme On 2000 July 14mentioning
confidence: 99%